Pattern of use of analgesics in a surgical unit - Mohammad Abdullah Al Masud; Syed Ashrafuzzaman; Md. Jalaluddin Iqbal (Bangladesh Pharmacological Society, 2009)
The present study was designed to evaluate the prescribing pattern of analgesics in post-operative patients in a surgical unit. Total number of 180 prescriptions containing analgesics was collected randomly. The only drug in the operation day that was used was pethidine (90.6%). Patients (9.4%) did not receive any analgesics in the operation day. Associated analgesics in the operation day were either tramadol (42.2 %) or ketorolac (54.4%). Only 3.3% did not receive any such drugs. In first post-operative day most of the patients received single drug tramadol (48.3%), ketorolac (38.9%) and pethidine (0.6%). In second, third, forth and fifth post-operative day most patients received tramadol (47.8%) (44.4%), (41.4%) and (33.2%) respectively. In sixth post-operative day most of the patients (81.1%) did not receive any analgesics. In this study tramadol was found to be widely used post-operative analgesics with minimal side effects and better adherence to this drug by the patient.